Spirituality review on mental health and psychiatric nursing - Lavorato Neto,Gabriel (2018)
ABSTRACT Objective: Gather the concepts, theories and interventions about spirituality, its nature and functions in mental health and psychiatric nursing. Method: A literature review proceeded on February 2016. It has integrated 214 studies published until December 2015 by crossing Spirituality and Psychiatric Nursing mesh terms in databases. Results: Conceptualization about spirituality and religion, their complexity in nursing research, education, and clinical approach; their functions to human being correlated to the purpose of life, transcendental connections, and support in mental health; the professional boundaries in address to spirituality in mental health scenery, and a descriptive literature recommendations and a instruments catalog. Conclusions: Spirituality in nursing mental health and psychiatry remains a theoretical problem, and has a clinical mischaracterized approach; recently publications try to promote a human and holistic trend in the practice, as a challenge to lead the current circumstances to valid nursing bases.